The role of identity in the development of depressive, anxiety, and psychosis symptoms in adolescents exposed to childhood adversity: research article - Samaey, Celine; Lecei, Aleksandra; Achterhof, Robin; Hagemann, Noëmi; Hermans, Karlijn S. F. M.; Hiekkaranta, Anu P.; Kirtley, Olivia J.; Reininghaus, Ulrich; Boets, Bart; Myin-Germeys, Inez; van Winkel, Ruud (Journal of adolescence, 2023)
Introduction Childhood adversity is a major risk factor for psychiatric disorders and has especially been associated with an admixture of depressive, anxiety, and psychosis symptoms. Identity formation, a main developmental task during adolescence, may be impacted by these adverse experiences and act as an important process in the association between childhood adversity and psychopathology. Methods We investigated the association between childhood adversity, identity formation, and depressive, anxiety, and psychosis symptoms cross-sectionally in 1913 Flemish adolescents between 11 and 20 years old (mean = 13.76, SD = 1.86). Adolescents completed questionnaires during the first wave of the SIGMA study between January 2018 and May 2019. Results Childhood interpersonal adversity was associated with increased identity confusion and decreased identity synthesis. Additionally, identity confusion was associated with increased self-reported levels of psychopathology and potentially mediated the association between childhood adversity and psychopathology. Conclusion This study highlights the importance of promoting healthy identity formation in adolescents with and without exposure to adverse childhood experiences.
Online veröffentlicht: 3. Februar 2023
Gesehen am 16.07.2024